Association of the Combined Effects between Insulin-Like Growth Factor-1 Gene Polymorphisms and Negative Life Events with Major Depressive Disorder among Chinese population in the Context of Oxidative Stress. (22nd April 2022) - Qiao, Zhengxue; Xie, Yunjia; Wu, Yongmei; Yang, Xiuxian; Qiu, Xiaohui; Zhou, Jiawei; Lu, Yuxin; Chen, Lu; Tong, Yuying; Xu, Jia; Li, Jiarui; He, Jingyun; et al.
Abstract : Background . Oxidative stress may be increased in a number of psychiatric disorders, including major depressive disorder (MDD). MDD has been shown to be related to insulin-like growth factor-1 (IGF-1) as well as to negative life events; exploring the interaction of IGF-1 polymorphisms and negative life events on the risk of MDD is needed. The aim of this study was to analyze the single and combined effects of IGF-1 polymorphisms (rs972936 and rs978458) and negative life events with MDD among Chinese population. Methods . 420 MDD patients (according to DSM-V) and 420 age- and gender-matched control subjects were recruited in a case-control study. Negative life events were assessed using standard rating scales. IGF-1 rs972936 and rs978458 were identified by sequencing. The chi-square (χ 2 ) tests were performed to explore the association of negative life events and IGF-1 polymorphisms with MDD. Results . Our results found that the negative life events were associated with the risk of MDD (P < 0.001 ; OR = 3.28, 95% CI: 2.19-4.85). The genotypes of IGF-1 were associated with the risk of MDD (P < 0.001 ); carrying the IGF-1 rs972936 C allele (OR = 1.53, 95% CI: 1.26-1.85) and rs978458 T allele (OR = 1.92, 95% CI: 1.58-2.34) had a higher risk of MDD. The combined effects between IGF-1 rs978458 and negative life events were associated with the risk of MDD (P < 0.05 ; OR = 2.94, 95% CI: 1.23-7.03), but IGF-1 rs972936 was not associated (P > 0.05 ). Conclusions . Based on the oxidative stress hypothesis, we confirm that carrying IGF-1 rs972936 C allele and rs978458 T allele have a higher risk of MDD and the combined effects between IGF-1 rs978458 and negative life events were associated with the risk of MDD among Chinese population.